Sinergi Zakat Dan Pajak Terhadap Perekonomian Indonesia - Ario Hernest Hadinata (Universitas Islam Nahdlatul Ulama Jepara, 2023)
This paper aims to introduce the concept of synergy between zakat and taxes as a new motivation to increase them in Indonesia. With this significant growth, zakat has the potential to become a tool for the economic and social welfare of society, and its position is as important as state revenue. Combined in an unbreakable partnership, zakat and taxes can help Indonesia's economy grow. The main reason for discussing how Zakat and Tax synergies is because zakat can help those who are less able to meet their basic needs. With this synergy, the people's economy will be supported, and the government will have more opportunities to allocate funds from the start for productive endeavors. Secondly, taxes will contribute to the foundation of the state's plan to develop and expand the economy. In this case, they will provide a stimulus that will expand the economy, which is likely to be felt and reflected in society. The orientation of this synergy is to direct so that zakat can be maximized in helping poverty alleviation, achieving professional and accountable zakat, as well as integration and synergy of all zakat institutions that can improve the Indonesian economy.